Diversity of ethnomycological knowledge and mushroom foraging culture in a small nation: case of Lithuania - Jurga Motiejūnaitė; Vita Džekčioriūtė; Ernestas Kutorga; Jonas Kasparavičius; Reda Iršėnaitė (BMC, 2024)
Abstract Background Even in mycophilic nations, mushroom foraging and use traditions may vary from region to region, making it part of cultural diversity and a source of traditional knowledge even in modern and changing societies. The main objective of our study was to investigate mushroom foraging and use traditions in major ethno-regions of Lithuania, to record and analyse whether and how biogeographical and ethno-cultural features influence these traditions, what is their biocultural significance, and whether they persist in the face of societal and environmental change. Methods The study conducted a survey among 106 respondents from eleven administrative units of Lithuania, representing four ethno-regions (Žemaitija, Suvalkija, Dzūkija and Aukštaitija, the latter divided into North and East). The age of the respondents ranged from 32 to 97 years (mean 70 years, median 68 years). Each respondent was asked six questions about mushroom species and mushroom foraging. The interviews were accompanied by 50 photographs of different mushroom species. The similarity between mushroom foragers' preferences in ethno-regions and the sets of mushroom species used for food and medicine was tested using cluster analysis. Clustering was carried out using Sørensen distances and the method of cluster mean linkage method. Results The number of mushroom species recognised per respondent was quite similar, with the lowest number of mushroom species recognised in Žemaitija and the highest in Eastern Aukštaitija. Species of no economic or other importance were not well recognised in any of the regions. The number of names applied to mushroom species varied from region to region and did not coincide with the popularity of mushrooms among mushroom pickers. The number of mushroom species used for food was also similar between regions, except for Dzūkija, which had the lowest number of species collected. Nine mushroom species were identified by respondents as medicinal mushrooms, the most popular being Amanita muscaria and Inonotus obliquus. When analysing the similarity of mushroom species collected for food and medicine, it was found that ethno-regions clustered into three distinct groups. Two groups depended on the prevailing forest types, while Žemaitija formed a separate cluster defined only by local traditions. Conclusions The work represents the largest study of ethnomycological tradition in Lithuania, covering major ethno-regions. We have found that ethnomycological knowledge and tradition are not influenced by any long-term historical events, ethnicity or religion, but rather by the prevailing forest types and regional ethno-culture. Knowledge of edible mushrooms is considered to be inherited from the older generation and is conservative regarding the changes in the set of species consumed and mushroom-related gastronomy. This is also reflected in the safety of mushroom consumption, as mushroom poisoning was very rare among the respondents. Economically insignificant mushrooms are not distinguished and overlooked by traditional mushroom pickers who are not a good source of information on rare or otherwise noteworthy species. However, from a biocultural point of view, mushrooms and mushroom-related traditions remain important for linguistic diversity, traditional knowledge systems and their transmission.